The Role of Entrepreneurial Strategies in Overcoming Economic Challenges in Regional Markets - Chshelokovskiy, Andrey (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
This research examines the role of entrepreneurial strategies in overcoming economic challenges across ten countries: the USA, Kazakhstan, UK, India, China, Poland, Brazil, Kenya, Saudi Arabia, and Turkey, during the period 2019–2023. By analyzing the impact of key strategies such as digital adoption, innovation, access to financing, and policy support, this study explores their influence on two key indicators: start-up survival rate and entrepreneurial growth rate. The research takes a quantitative approach that employs panel data regression, and utilizes secondary data from global economic databases. Results show that entrepreneurial activity is strong worldwide, but sustainability of start-ups dramatically differs between developed, emerging and developing economies. Higher Entrepreneurial growth rate and Start up survival rate is observed in the countries with more robust institutional support and access to resources. Lastly the study presents the possible recommendations for nurturing entrepreneurial ecosystems for sustainable business growth and economic resilience especially in the emerging and the developing markets.